2021
DOI: 10.3390/ijgi10030130
|View full text |Cite
|
Sign up to set email alerts
|

The Sketch Map Tool Facilitates the Assessment of OpenStreetMap Data for Participatory Mapping

Abstract: A worldwide increase in the number of people and areas affected by disasters has led to more and more approaches that focus on the integration of local knowledge into disaster risk reduction processes. The research at hand shows a method for formalizing this local knowledge via sketch maps in the context of flooding. The Sketch Map Tool enables not only the visualization of this local knowledge and analyses of OpenStreetMap data quality but also the communication of the results of these analyses in an understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Some papers focused on multiple countries, which have been counted for each country. 12 articles had a global focused and could not be assigned to a country Adopting ethnographic methods, including focus group discussion and key informant interviews, offers an opportunity to unveil local knowledge that can improve policies in reducing disaster risk (Cronin et al 2004;Glaser et al 2008;Kelman et al 2012;Tiepolo and Braccio 2017;Ebhuoma 2020;Klonner et al 2021;Pauli et al 2021). These methods use past experiences of locals to discover facts, relationships, and new 'truths' surrounding vulnerability to hazards (Mercer and Kelman 2009).…”
Section: Existing Practices For Integrating Knowledgesmentioning
confidence: 99%
“…Some papers focused on multiple countries, which have been counted for each country. 12 articles had a global focused and could not be assigned to a country Adopting ethnographic methods, including focus group discussion and key informant interviews, offers an opportunity to unveil local knowledge that can improve policies in reducing disaster risk (Cronin et al 2004;Glaser et al 2008;Kelman et al 2012;Tiepolo and Braccio 2017;Ebhuoma 2020;Klonner et al 2021;Pauli et al 2021). These methods use past experiences of locals to discover facts, relationships, and new 'truths' surrounding vulnerability to hazards (Mercer and Kelman 2009).…”
Section: Existing Practices For Integrating Knowledgesmentioning
confidence: 99%
“…This message resonates well with the overall image emerging from the survey of the three perspectives above-while each perspective is distinct, it is not independent from the others with clear interrelations existing between them: utilizing OSM data first requires an understanding of their quality (and quality may be part of the application, as showed in [28] or may be improved through applications of other data [23]); quality needs to be interpreted in light of the dynamics of the data production process through increased engagement; and understanding dynamics, e.g., through increased engagement, may lead to a refocusing of the scientific effort. Conceptualizing the study of OSM as 'OSM science' may provide utility in this context by framing OSM-related scientific studies not as a set of individualized efforts but as a unified approach with shared objectives and concerns that can be formalized through dedicated theoretical frameworks relevant even for novice and incidental OSM researchers.…”
mentioning
confidence: 55%
“…Madubedube et al [27], on the other hand, present an intrinsic quality analysis using patterns identified in the data through unsupervised learning which provide insights regarding their quality, e.g., "that the behavior of a small group of active contributors makes it possible to characterize the quality of an entire datasets" (page 14) due to participation inequality. Klonner et al [28] also follow an intrinsic approach, yet the authors focus in this paper not only on quality analysis but also on the communication of results to end-users. They present the Sketch Map Tool, which relies on OSM data to perform multiple operations required for participatory mapping, including intrinsic data quality analysis.…”
mentioning
confidence: 99%
“…Another method could be sketch maps (Klonner et al, 2021): people mark their personal flood risk knowledge of local areas in paper maps, which are afterwards automatically georeferenced and ready to be used for further geospatial analysis, combined with other data, such as technical sensor data. Data are portrayed on a Web portal, and thus, citizens can access and see their own contributions, a process that could lead to motivation for further engagement.…”
Section: Resultsmentioning
confidence: 99%